Extensive Synovial Chondromatosis of the Temporomandibular Joint Extending to the Cranial Base - Chi-Heon Sung; Seo-Young An; Hae-Seo Park; Wonae Lee; Moon-Young Kim (Diagnostics, 2024)
A 42-year-old male presented to the Department of Oral and Maxillofacial Surgery with the chief complaint of pain and stiffness in the right temporomandibular joint (TMJ). The patient’s height was 174 cm and his body weight was 65 kg. The patient’s occupation was heavy equipment operator. According to the patient, the pain had initiated a week prior to his first visit and was exacerbated during mastication. Evaluation of the range of motion revealed extensive crepitus along the right TMJ. The active and passive range of motion were measured at 45 mm and 42 mm, respectively, indicating adequate mouth-opening capacity. Occlusion was also favorable, and no other clinical symptoms were shown intraorally.